2019
DOI: 10.1121/1.5126003
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional finite element simulation of acoustic propagation in spiral bubble net of humpback whale

Abstract: JASApossible enhancements that the time-varying nature of the call during feeding could 23give to the whale in this mechanism for the bubble net feeding by humpback whales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Besides idealized cases, many papers in this special issue consider realistic environments, such as estuaries (Reeder and Lin, 2019) and lakes , the Hudson Canyon (Ballard and Sagers, 2019;Barclay and Lin, 2019), the East China Sea (Porter, 2019), nonlinear internal waves (Dossot et al, 2019;Duda et al, 2019), the continental slope (Dall'Osto, 2019), the Mid-Atlantic Ridge (Oliveira and Lin, 2019), the abyssal seafloor (Stephen et al, 2019), and even bubble nets produced by foraging humpback whales (Qing et al, 2019). These studies indeed provide useful insights to the understanding of 3D acoustic effects observed in the real world, such as time-varying features caused by salt wedges in estuaries and nonlinear internal waves in the continental shelf area, as well as bathymetric effects on 3D focusing, defocusing, and diffraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides idealized cases, many papers in this special issue consider realistic environments, such as estuaries (Reeder and Lin, 2019) and lakes , the Hudson Canyon (Ballard and Sagers, 2019;Barclay and Lin, 2019), the East China Sea (Porter, 2019), nonlinear internal waves (Dossot et al, 2019;Duda et al, 2019), the continental slope (Dall'Osto, 2019), the Mid-Atlantic Ridge (Oliveira and Lin, 2019), the abyssal seafloor (Stephen et al, 2019), and even bubble nets produced by foraging humpback whales (Qing et al, 2019). These studies indeed provide useful insights to the understanding of 3D acoustic effects observed in the real world, such as time-varying features caused by salt wedges in estuaries and nonlinear internal waves in the continental shelf area, as well as bathymetric effects on 3D focusing, defocusing, and diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of numerical models to generate accurate predictions of 3D acoustic propagation and scattering is also highlighted in this special issue. These models include finiteelement methods by Qing et al (2019) to calculate acoustic pressure and particle motion induced by foraging whale vocalizations inside the bubble net, and by Lecoulant et al (2019) to calculate seismo-acoustic propagation in the ocean and seabed generated by earthquakes. Another group of numerical models uses the parabolic-equation method, which was first introduced to underwater acoustics by Hardin and Tappert (1973) and Tappert (1974).…”
Section: Introductionmentioning
confidence: 99%
“…F lexible manipulation of bubbles in underwater environments is a crucial and fascinating survival skill of many creatures, such as respiration, 1,2 self-defense, 3,4 and predation. 5,6 Meanwhile, the dynamic manipulation of bubbles is also ubiquitous and critical to a wide range of applications in both scientific and industrial fields, such as gas evolution reactions, 7−9 heat transfer, 10−12 greenhouse gas collection, 13 fermentation, 14 and drug delivery. 14−16 However, limitations from buoyancy inhibition, hydrostatic pressure, gas dissolving, and easy deformability block the way of gas bubbles toward smart manipulation.…”
mentioning
confidence: 99%
“…Flexible manipulation of bubbles in underwater environments is a crucial and fascinating survival skill of many creatures, such as respiration, , self-defense, , and predation. , Meanwhile, the dynamic manipulation of bubbles is also ubiquitous and critical to a wide range of applications in both scientific and industrial fields, such as gas evolution reactions, heat transfer, greenhouse gas collection, fermentation, and drug delivery. However, limitations from buoyancy inhibition, hydrostatic pressure, gas dissolving, and easy deformability block the way of gas bubbles toward smart manipulation. , The wide range adoption of conventional technologies to manipulate bubbles, including mechanical agitation, , sonication, , or adjusting fluid viscosity/velocity, , are largely shadowed by high-energy consumption, complex conducting systems, and inaccurate control of bubble behavior. Despite recent efforts in gradient-based topography and wettability, which have demonstrated the feasibility of a spontaneous, unidirectional, and long-distance bubble delivery, the motion of underwater bubbles has always been limited in one single direction, i.e.…”
mentioning
confidence: 99%